Islamic Educational Values in the Characters of the Pandawa Wayang to Shape Pancasila Students Profile - Teguh Santosa Dody Suyatno; Betty Mauli Rosa Bustam (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Many young generations today are influenced by the development of the times to show deviant behavior that is not in accordance with Islamic law, such as dressing, behaving, and communicating. This research aims to uncover and analyze the values of Islamic education contained in the Pandawa puppet characters and their relevance in shaping the profile of Pancasila Students at SMP N 4 Pandak. This study uses a qualitative approach with literature study methods and participatory observation on the implementation of these values in learning and student activities. The results of the study show that the character of Pandawa can be an effective educational medium in internalizing religious and moral values that are in line with the dimensions of Pancasila Students, such as faith and fear of Allah, global diversity, cooperation, independence, critical reasoning, and creativity. The understanding of Yogyakarta madrasah students towards the values of Islamic education in the character of Wayang Pandawa is to have a good character that is in accordance with the teachings of Islam with commendable qualities. Implementation of Pancasila student values by Yogyakarta madrasah students through Wayang Pandawa aims to exemplify good character, preserve cultural heritage, and shape morally and intellectually superior future generations.